Prospects of herbicide-tolerant rice under Indian perspective - Saha, Sanjoy; Munda, Sushmita; Jangde, Hemant Kumar (Indian Farming, 2018)
Herbicides-tolerant rice has a great potential in the simplification of weed management. It must be emphasized that the risk from herbicide-tolerante rice should be carefully evaluated prior to releasing the herbicide-tolerante rice into a cropping system, especially when the herbicide-tolerante rice possess weedy characters or may outcross to related weeds. In commercially grown herbicide-tolerante rice, precautions need to be taken in the management strategies to prevent the development of naturally-resistant weeds. Many have concerns that genetically modified herbicide tolerant rice would bring reduction of biodiversity, and then affect the balance of agro-ecosystem; and exogenous gene of genetically modified herbicide-tolerante rice would escape to cultivated rice, weedy rice and its wild relatives through gene flow. To meet people’s demand of food and ensure safety to people and environment, the research about the possible effects of genetically modified herbicidetolerante rice on biodiversity is urgent and important.